WAO - ARIA consensus on chronic cough: Executive summary - Philip W. Rouadi, MD; Samar A. Idriss, MD; Jean Bousquet, MD, PhD; Mario Morais-Almeida, MD; Cecilio R. Azar, MD; Mona Sulaiman Al-Ahmad, MD; Anahí Yáñez, MD; Maryam Ali Y Al-Nesf, MD, MSc; Talal M. Nsouli, MD; Sami L. Bahna, MD, DrPH; Eliane Abou-Jaoude, MD; Fares H. Zaitoun, MD; et al. (World Allergy Organization Journal, 2025)
Acute cough is a highly prevalent symptom in clinical practice. Chronic cough is a complex disease with significant impact on quality of life. The mechanistic pathways of chronic cough in cough-comorbid clinical phenotypes are elusive. Mounting evidence suggests presence of a hypersensitive cough reflex and implication of transient receptor potential channels and P2X receptors in cough neuronal pathways. Previously, the World Allergy Organization (WAO)/Allergic Rhinitis and its Impact on Asthma (ARIA) Joint Committee on Chronic Cough published updated experimental and clinical data on chronic cough, in addition to a multidisciplinary care pathway approach to its management. The goal of this manuscript is to provide clinicians with a succinct summary of chronic cough pathophysiology, clinical phenotypes, and management strategies in both primary and cough specialty care. This executive summary is a primer for clinicians on chronic cough. Increasing awareness on the topic among primary care physicians will improve the outcome of management of patients with chronic cough.